2001
DOI: 10.1054/bjoc.2000.1528
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity is related to p53 mutations and smoking in lung cancer

Abstract: Summary Carcinogenesis results from an accumulation of several genetic alterations. Mutations in the p53 gene are frequent and occur at an early stage of lung carcinogenesis. Loss of multiple chromosomal regions is another genetic alteration frequently found in lung tumours. We have examined the association between p53 mutations, loss of heterozygosity (LOH) at frequently deleted loci in lung cancer, and tobacco exposure in 165 tumours from non-small cell lung cancer (NSCLC) patients. A highly significant asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
10
37
0
Order By: Relevance
“…In addition, purified genomic DNA isolated from microdissected DNAs could potentially reduce the masking effects of nontumourous genomic DNA contaminated in tissue specimens and increased LOH frequency. Previous studies have shown that the loss of 3p14.2 is more common in squamous cell carcinomas than in adenocarcinomas (Tsuchiya et al, 1992;Testa et al, 1994;Zienolddiny et al, 2001). Our data are consistent with this association (Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, purified genomic DNA isolated from microdissected DNAs could potentially reduce the masking effects of nontumourous genomic DNA contaminated in tissue specimens and increased LOH frequency. Previous studies have shown that the loss of 3p14.2 is more common in squamous cell carcinomas than in adenocarcinomas (Tsuchiya et al, 1992;Testa et al, 1994;Zienolddiny et al, 2001). Our data are consistent with this association (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between LOH at the FHIT gene locus and the patients' survival was different in different studies (Fong et al, 1997;Sozzi et al, 1997Sozzi et al, , 1998Burke et al, 1998;Tomizawa et al, 1998). Loss of heterozygosity at the FHIT gene locus in smokers has occurred more frequently than that in nonsmokers Zienolddiny et al, 2001). It was also reported that lack of Fhit staining correlates with LOH at the FHIT 3p14.2 locus, but not at other loci on 3p (Geradts et al, 2000).…”
mentioning
confidence: 97%
“…As in the reports mentioned before (Marchetti et al, 1998;Geradts et al, 2000), Fhit expression was not correlated to the abnormality of p53 in smoking patients. A recent study (Zienolddiny et al, 2001) indicated that LOH at 3p, 5q, 9p, 11p, and 17p regions were interdependent and highly associated with mutated TP53 gene in smokers. The significant association of Fhit and p53 protein expressions with smokers in the present study is perhaps related to the size of this series.…”
Section: Discussionmentioning
confidence: 98%
“…Alteration of the TP53 gene may be involved in the initiation, development, progression, and invasion of lung cancer (Caamano et al, 1991;Sozzi et al, 1992;Marchetti et al 1993;Fontanini et al, 1994). Even though correlation of p53 protein expression with clinical and biological characteristics of lung cancer has been extensively studied, the results of these studies are quite diverse (Top et al, 1995;Passlick et al, 1995;Dalquen et al, 1996;Lee et al 1999;Garinis et al, 2001;Zienolddiny et al, 2001). The results of this study indicated that p53 expression was closely related to distant metastasis of the overall NSCLCs and the adenocarcinoma subtype; and p53 was especially useful as a prognostic factor in adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation